CULTURAL DIALOG AS A MULTI-COMPONENT MEANS OF FORMING A TOLERANT PERSONALITY - S. Hajrullina, Alfira; F. Dautov, Gumar; R. Mugtasimova, Gulnaz; A. Mukimova, Nasima (Revista Gênero e Interdisciplinaridade, 2021)
This paper considers the possibilities of cultural dialog in the formation and education of a tolerant personality. Modern educational paradigms are studies in terms of humanization and humanitarization of education; creative use of  tolerance; issues of formation of moral values based on meaningful value bases of human life and society; value attitude to a person; search for the meaning of life through the characters on the example of the works of Razil Valeev. The analysis of scientific literature allows identifying a number of its features: the upbringing of a person as a subject of action; finding a dominant inside the life itself; the formation of a tolerant personality in the context of a cultural dialog, and others. The authors analyze the prose of the famous Tatar writer Razil Valeev. The research complements the theoretical space of the actual pedagogical problem, makes it possible to consider the research  in a practical aspect.  This is because the proposed model can be used by teachers, school teachers at lessons of national pedagogy, native literature and extracurricular activities for educational work